Full-biodegradable thermal shrinkage film for commercial zero cigarettes and preparation method of full-biodegradable thermal shrinkage film

By modified polystrackic acid (PLA) mother material and multi -segment heating, two -way stretching technology, the whole biodegradable thermal contraction membrane with high transparency, strong tensile strength and good biodegradation is prepared to solve the existing thermal reduction membrane in transparency , Insufficient strength, toughness, and biological decomposition rates have achieved more efficient packaging performance and lower environmental impacts.

CN119331396APending Publication Date: 2025-01-21CHENGDU HUASHU YUNLIAN INFORMATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411410146.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing biodegradable heat shrink films have shortcomings in terms of transparency, strength, toughness and biodegradation rate, which cannot meet the packaging needs in various fields and pose a certain burden to the environment.

Method used

Using modified polystrackic acid (PLA) mother material, by adding measuring agglomerations, lipolase, cellulose, inorganic calcium powder, epoxy soybean oil and antioxidants, combined with multi -segment heating and bidirectional stretching technology, Prepare all biodegradable thermal film with high transparency, strong tensile strength, and good biodegradability.

Benefits of technology

The heat shrinkable film achieves high transparency, high shrinkage, high toughness and strong cold resistance, with low biological toxicity and excellent degradation effect. It is suitable for a variety of packaging fields and reduces the burden on the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention belongs to the technical field of materials, and discloses a full-biodegradable heat shrinkage film for commercial zero cartons of cigarettes and a preparation method thereof.The full-biodegradable heat shrinkage film is prepared from, by weight, 50-60 parts of modified PLA master batch, 5-10 parts of lubricant, 4-8 parts of polytrimethylene terephthalate, 3-5 parts of chain extender, 3-5 parts of anti-blocking agent and 20-30 parts of filling master batch; the preparation method of the modified PLA master batch comprises the following steps: carrying out first drying on a toughening plasticizer to obtain a dried toughening plasticizer; the dried toughening plasticizer, polylactic acid, aliphatic enzyme, cellulose, inorganic calcium powder, epoxidized soybean oil and an antioxidant are subjected to first mixing and then flow out, and a plastic melt is obtained; and carrying out first cooling, second drying and grain-sized packaging on the plastic melt to obtain the modified PLA master batch. The modified biodegradable material and the biological auxiliary agent which are high in strength and good in compatibility are introduced into the full-biodegradable heat shrinkage film, so that the full-biodegradable heat shrinkage film has excellent mechanical properties and transparency, is good in biodegradability and low in biotoxicity and can be used as a packaging material in the tobacco industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of material technology, and specifically relates to a fully biodegradable heat shrinkable film for commercial cigarette cartons and a preparation method thereof. Background Art

[0002] At present, biodegradable materials have been widely studied and applied in the fields of packaging, textile fibers, agriculture, forestry, animal husbandry and fishery, automobile industry, electronic appliances and medical biodegradable materials.

[0003] Biodegradable packaging materials refer to a type of plastic whose various properties meet the use requirements during the storage period and can eventually be decomposed by microorganisms into CO2, water and inorganic substances, achieving zero pollution to the environment. They are considered to be one of the effective ways to solve the problem of plastic pollution. At present, most of the biodegradable heat shrink films promoted, although they meet environmental protection requirements, still face problems such as low transparency, low strength, poor toughness and poor packaging effect, and the biodegradation rate is not high. For example, a fully biodegradable packaging film in the prior art has a right-angle tear force converted into a right-angle tear strength of 76kN / m in the longitudinal direction and 68kN / m in the transverse direction. Its elongation at break is 58% in the longitudinal direction and 18% in the transverse direction. Its biodegradation rate is only more than 60%, which cannot be applied to packaging in various fields and will still cause a certain burden on the environment.

[0004] Therefore, a novel biodegradable heat shrinkable film is needed to overcome its current technical defects. Summary of the invention

[0005] The problem that the present application aims to solve is to provide a fully biodegradable heat shrinkable film for commercial cigarettes and a preparation method thereof. The fully biodegradable heat shrinkable film introduces modified biodegradable materials and bio-auxiliaries with high strength and good compatibility, has excellent mechanical properties and transparency, and has good biodegradability and low biological toxicity, and can be used as a packaging material in the tobacco industry.

[0006] In order to solve the above technical problems, this application adopts the following technical solutions:

[0007] On the one hand, the present application provides a fully biodegradable heat shrinkable film for commercial cigarettes, wherein the fully biodegradable heat shrinkable film comprises, by weight:

[0008]

[0009] Wherein, the method for preparing the modified PLA masterbatch comprises:

[0010] The toughening plasticizer is first dried to obtain a dry toughening plasticizer; the dry toughening plasticizer, polylactic acid (PLA), lipase, cellulose, inorganic calcium powder, epoxy soybean oil and antioxidant are first mixed and then discharged to obtain a plastic melt; and the plastic melt is first cooled, second dried and pelletized and packaged to obtain the modified PLA masterbatch.

[0011] In the above technical scheme, the modified PLA masterbatch can make the final heat shrinkable film have excellent tensile strength, impact resistance, heat shrinkage and degradability; polytrimethylene terephthalate (Ptt) has high heat resistance, toughness, fatigue resistance, self-lubrication and low friction coefficient, etc., which can provide stronger physical support and stability for the heat shrinkable film, and can also make the heat shrinkable film have certain elasticity and retraction while maintaining its beauty; toughening plasticizers, aliphatic enzymes, cellulose, inorganic calcium powder, epoxy soybean oil and antioxidants are used to modify polylactic acid, so that the final heat shrinkable film can have better toughness and degradability.

[0012] In some embodiments, the modified PLA masterbatch comprises, by weight:

[0013]

[0014] In the above technical solution, the weight proportions of the dry toughening plasticizer, polylactic acid, lipase, cellulose, inorganic calcium powder, epoxy soybean oil and antioxidant are limited, so that the final heat shrinkable film has better toughness and degradability.

[0015] In some embodiments, the lubricant comprises stearic acid.

[0016] In some embodiments, the chain extender comprises ADR-4368.

[0017] In some embodiments, the opening agent includes at least one of EBS, oleamide and polyethylene wax.

[0018] In some embodiments, the filler masterbatch includes at least one of corn flour and talc.

[0019] In some embodiments, the lipphatic enzyme comprises Candida lipase.

[0020] In the above technical solution, the limited lipaphatic enzyme can make the final heat shrinkable film have a better degradation effect, and at the same time can improve the contact effect between the heat shrinkable film and the product, making the packaging more compact and uniform.

[0021] In some embodiments, the antioxidant includes antioxidant 1076.

[0022] In the above technical solution, limiting the types of antioxidants can better prevent or delay the oxidation reaction of the heat shrinkable film, so that the heat shrinkable film has a longer service life.

[0023] In some embodiments, the first mixing is carried out in a first twin-screw extruder, the aspect ratio of the first twin-screw extruder is 40:1, the barrel temperature of the first twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the first twin-screw extruder is 80-90r / min.

[0024] In the above technical solution, the use of a multi-stage heated twin-screw extruder can better mix the dry toughening plasticizer, polylactic acid, lipase, cellulose, inorganic calcium powder, epoxy soybean oil, antioxidant and polylactic acid, so that the polylactic acid has a better modification effect.

[0025] In some embodiments, the first drying method includes cold air drying. For example, the first drying temperature is 15° C. and the first drying time is 2 hours.

[0026] In some embodiments, the first cooling method includes water tank cooling. For example, the temperature of the water tank is 4° C., and the first cooling time is 5 minutes.

[0027] In some embodiments, the second drying method includes cold air drying. For example, the temperature of the cold air is 15° C., and the second drying time is 2 hours.

[0028] In some embodiments, the method for preparing the toughening plasticizer comprises: adding a diol and a catalyst system to a dibasic acid to carry out an esterification reaction to obtain a milky white homogeneous liquid; and adding lactic acid to the milky white homogeneous liquid to carry out an ester exchange condensation reaction to obtain the toughening plasticizer.

[0029] In the above technical solution, the toughening plasticizer prepared using diols, lactic acid and dibasic acid has excellent ductility, elongation, heat resistance, impact resistance and biodegradability, and can improve the brittleness of PLA when melt-blended with PLA.

[0030] In some embodiments, the molar ratio of the dibasic acid to the diol is 1:1-3.

[0031] In some embodiments, the weight ratio of the lactic acid to the milky white homogeneous liquid is 1:4-6.

[0032] In the above technical scheme, the molar ratio of diol to dibasic acid and the weight ratio of lactic acid to milky white homogeneous liquid are limited, so that the final heat shrinkable film has better ductility, elongation, heat resistance, impact resistance and biodegradability.

[0033] In some embodiments, the glycol comprises ethylene glycol.

[0034] In the above technical solution, limiting the type of diol can make the final heat shrinkable film have better ductility, elongation, heat resistance, impact resistance and biodegradability.

[0035] In some embodiments, the dibasic acid comprises succinic acid.

[0036] In the above technical solution, limiting the type of dibasic acid can make the final heat shrinkable film have better ductility, elongation, heat resistance, impact resistance and biodegradability.

[0037] In some embodiments, the catalyst system includes a system consisting of isopropyl titanate and methanesulfonic acid.

[0038] In the above technical scheme, the catalyst system composed of isopropyl titanate and methanesulfonic acid has a better catalytic effect when preparing toughening plasticizers. At the same time, isopropyl titanate decomposes at high temperature to generate a titanium dioxide film layer, which can improve the heat resistance and mechanical properties of the toughening plasticizer.

[0039] In some embodiments, the esterification reaction is carried out under a nitrogen environment at normal pressure, the temperature of the esterification reaction is 190° C. to 210° C., and the time of the esterification reaction is 5 to 6 hours.

[0040] In the above technical solution, the esterification reaction is carried out in a nitrogen environment, which can reduce the interference of oxygen and other impurities on the esterification reaction, so that the esterification reaction is carried out in a more optimized reaction path, thereby improving the overall reaction efficiency.

[0041] In some embodiments, the transesterification polycondensation reaction is carried out under a 40 kPa nitrogen environment, the temperature of the transesterification polycondensation reaction is 210° C. to 240° C., and the time of the transesterification polycondensation reaction is 1 to 2 hours.

[0042] In the above technical scheme, the ester exchange polycondensation reaction is carried out in a low-pressure nitrogen environment, which can not only reduce the interference of oxygen and other impurities on the ester exchange polycondensation reaction, but the low-pressure environment also helps to remove small molecules produced in the reaction, thereby improving the efficiency of the ester exchange polycondensation reaction and the purity of the product.

[0043] On the other hand, the present application provides a method for preparing the above-mentioned fully biodegradable heat shrinkable film for commercial cigarettes. The method comprises the following steps: performing a second mixing, extrusion and a second cooling on the modified PLA masterbatch, lubricant, polytrimethylene terephthalate, chain extender, opening agent and filler masterbatch to obtain a cast sheet; and biaxially stretching, winding and slitting the cast sheet to obtain the fully biodegradable heat shrinkable film.

[0044] In the above technical solution, biaxial stretching of the cast sheet can make the final heat shrinkable film have excellent properties such as high transparency, high shrinkage, high toughness and strong cold resistance.

[0045] In some embodiments, the second mixing is carried out in a second twin-screw extruder, the aspect ratio of the second twin-screw extruder is 40:1, the barrel temperature of the second twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the second twin-screw extruder is 80-90r / min.

[0046] In some embodiments, the second cooling method comprises drum cooling.

[0047] In some embodiments, the temperature of the biaxial stretching is 80-90° C., the transverse stretching ratio is 3 times, and the longitudinal stretching ratio is 2 times.

[0048] This application has the following beneficial effects:

[0049] (1) The use of toughening plasticizers and bio-additives to modify PLA not only makes the final commercial fully biodegradable heat shrink film for cigarettes have excellent degradation performance, but also better toughness and strength.

[0050] (2) Mixing PLA masterbatch with lubricants, Ptt, chain extenders and other raw materials can provide stronger physical support and stability for the fully biodegradable heat shrinkable film for commercial cigarette cartons, and can also make the heat shrinkable film have better transparency, while improving the wrapping properties of the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0051] (3) The use of multi-stage heating can enable various raw materials to be fully mixed and reacted when preparing the modified PLA masterbatch, thereby improving the modification effect of the PLA masterbatch.

[0052] (4) The use of biaxial stretching technology can improve the transparency, shrinkage, toughness and cold resistance of the fully biodegradable heat shrink film used for commercial cigarette packs.

[0053] (5) The fully biodegradable heat shrinkable film for commercial cigarettes obtained in this application has excellent tear resistance and tensile strength, high transparency, extremely low biological toxicity, excellent degradation effect, and excellent wrapping performance. It is a very potential biodegradable heat shrinkable film that can be used for packaging in multiple fields in the future. DETAILED DESCRIPTION

[0054] The technical solutions in some embodiments of the present disclosure are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0055] In the following, the terms "first", "second", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features.

[0056] Example 1

[0057] Prepare the toughened plasticizer as follows:

[0058] S11. Under normal pressure nitrogen environment, 31 parts of ethylene glycol, 10 parts of isopropyl titanate and 5 parts of methylsulfuric acid were added to 52 parts of malonic acid, and the esterification reaction was carried out at 190° C. for 5 hours to obtain a milky white homogeneous liquid;

[0059] S12. After reducing the pressure of the nitrogen environment to 40 kPa using an oil pump, 10 parts of lactic acid are added to 40 parts of the milky white homogeneous liquid, and the temperature is raised to 210° C. to carry out an ester exchange polycondensation reaction for 1 hour to obtain the toughening plasticizer.

[0060] Example 2

[0061] Prepare the toughened plasticizer as follows:

[0062] S11. Under normal pressure nitrogen environment, 62 parts of ethylene glycol, 10 parts of isopropyl titanate and 5 parts of methylsulfuric acid were added to 52 parts of malonic acid, and the esterification reaction was carried out at 200 ° C for 5.5 hours to obtain a milky white homogeneous liquid;

[0063] S12. After reducing the pressure of the nitrogen environment to 40 kPa using an oil pump, 10 parts of lactic acid are added to 50 parts of the milky white homogeneous liquid, and the temperature is raised to 225° C. to carry out an ester exchange polycondensation reaction for 1.5 hours to obtain the toughening plasticizer.

[0064] Example 3

[0065] Prepare the toughened plasticizer as follows:

[0066] S11. Under normal pressure nitrogen environment, 93 parts of ethylene glycol, 10 parts of isopropyl titanate and 5 parts of methylsulfuric acid were added to 52 parts of malonic acid, and the esterification reaction was carried out at 210° C. for 6 hours to obtain a milky white homogeneous liquid;

[0067] S12. After reducing the pressure of the nitrogen environment to 40 kPa using an oil pump, 10 parts of lactic acid are added to 60 parts of the milky white homogeneous liquid, and the temperature is raised to 240° C. to carry out an ester exchange polycondensation reaction for 2 hours to obtain the toughening plasticizer.

[0068] Example 4

[0069] Follow the steps below to prepare modified PLA masterbatch:

[0070] S21. The toughening plasticizer prepared in Example 1 was dried in cold air at 15°C for 2h to obtain a dry toughening plasticizer;

[0071] S22. 4 parts of the dry toughening plasticizer, 50 parts of PLA, 2 parts of Candida lipase, 10 parts of cellulose, 4 parts of inorganic calcium powder, 5 parts of epoxidized soybean oil and 0.2 parts of antioxidant 1076 are added to a twin-screw extruder with a barrel temperature of 165°C for the first stage, 170°C for the second stage, 175°C for the third stage, 180°C for the fourth stage, 175°C for the fifth stage and 165°C for the sixth stage, and the length-to-diameter ratio is 40:1, and the mixture is mixed and then discharged to obtain a plastic melt;

[0072] S23. The plastic melt is cooled in a water tank at 4° C. for 5 min, then dried in cold air at 15° C. for 2 h, and pelletized and packaged to obtain the modified PLA masterbatch.

[0073] Example 5

[0074] Follow the steps below to prepare modified PLA masterbatch:

[0075] S21. The toughening plasticizer prepared in Example 2 was dried in cold air at 15°C for 2h to obtain a dry toughening plasticizer;

[0076] S22. 5 parts of the dry toughening plasticizer, 55 parts of PLA, 3 parts of Candida lipase, 12 parts of cellulose, 6 parts of inorganic calcium powder, 10 parts of epoxidized soybean oil and 0.4 parts of antioxidant 1076 are added to a twin-screw extruder with a barrel temperature of 165°C for the first stage, 170°C for the second stage, 175°C for the third stage, 180°C for the fourth stage, 175°C for the fifth stage and 165°C for the sixth stage, and the length-to-diameter ratio is 40:1, and the mixture is mixed and then discharged to obtain a plastic melt;

[0077] S23. The plastic melt is cooled in a water tank at 4° C. for 5 min, then dried in cold air at 15° C. for 2 h, and pelletized and packaged to obtain the modified PLA masterbatch.

[0078] Example 6

[0079] Follow the steps below to prepare modified PLA masterbatch:

[0080] S21. The toughening plasticizer prepared in Example 3 was dried in cold air at 15°C for 2h to obtain a dry toughening plasticizer;

[0081] S22. 6 parts of the dry toughening plasticizer, 60 parts of PLA, 4 parts of Candida lipase, 15 parts of cellulose, 8 parts of inorganic calcium powder, 15 parts of epoxidized soybean oil and 0.6 parts of antioxidant 1076 were added to a twin-screw extruder with a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and the length-to-diameter ratio was 40:1, and the mixture was mixed and then discharged to obtain a plastic melt;

[0082] S23. The plastic melt is cooled in a water tank at 4° C. for 5 min, then dried in cold air at 15° C. for 2 h, and pelletized and packaged to obtain the modified PLA masterbatch.

[0083] Example 7

[0084] Follow the steps below to prepare the fully biodegradable heat shrink film for commercial cigarette cartons:

[0085] S31. 50 parts of the modified PLA masterbatch prepared in Example 4, 5 parts of stearic acid, 4 parts of polytrimethylene terephthalate, 3 parts of ADR-4368, 3 parts of oleic acid amide and 20 parts of corn flour are added into a twin-screw extruder with a length-to-diameter ratio of 40:1 and a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and mixed and extruded at 80 r / min, and then cooled by a rotary drum to obtain a cast sheet.

[0086] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 80° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0087] Example 8

[0088] Follow the steps below to prepare a fully biodegradable heat shrink film for commercial cigarette packs:

[0089] S31. 55 parts of the modified PLA masterbatch prepared in Example 5, 8 parts of stearic acid, 6 parts of polytrimethylene terephthalate, 4 parts of ADR-4368, 4 parts of EBS and 25 parts of talc are added to a twin-screw extruder with a length-to-diameter ratio of 40:1 and a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and mixed and extruded at 85 r / min, and then cooled by a rotary drum to obtain a cast sheet.

[0090] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 85° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0091] Example 9

[0092] Follow the steps below to prepare a fully biodegradable heat shrink film for commercial cigarette packs:

[0093] S31. 60 parts of the modified PLA masterbatch prepared in Example 6, 10 parts of stearic acid, 8 parts of polytrimethylene terephthalate, 5 parts of ADR-4368, 5 parts of polyethylene wax, 15 parts of corn flour and 15 parts of talcum powder are added to a twin-screw extruder with a length-to-diameter ratio of 40:1 and a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and mixed and extruded at 90 r / min, and then cooled by a rotary drum to obtain a cast sheet.

[0094] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 90° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0095] Comparative Example 1

[0096] Follow the steps below to prepare the fully biodegradable heat shrink film for commercial cigarette cartons:

[0097] S31. 50 parts of PLA masterbatch, 5 parts of stearic acid, 4 parts of polytrimethylene terephthalate, 3 parts of ADR-4368, 3 parts of oleic acid amide and 20 parts of corn flour are added into a twin-screw extruder with a length-to-diameter ratio of 40:1 and a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and the mixture is extruded at 80 r / min, and then cooled by a rotary drum to obtain a cast sheet.

[0098] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 80° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0099] Comparative Example 2

[0100] Follow the steps below to prepare the fully biodegradable heat shrink film for commercial cigarette cartons:

[0101] S31. 50 parts of the modified PLA masterbatch prepared in Example 4, 5 parts of stearic acid, 4 parts of poly(trimethylene terephthalate), 3 parts of ADR-4368, 3 parts of oleic acid amide, and 20 parts of corn flour are added to a twin-screw extruder with a barrel temperature of 180°C and a length-to-diameter ratio of 40:1, mixed and extruded at 80 r / min, and cooled by a rotary drum to obtain a cast sheet.

[0102] S32. The cast sheet is stretched 3 times in the transverse direction and 2 times in the longitudinal direction at 80° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0103] Comparative Example 3

[0104] Follow the steps below to prepare the fully biodegradable heat shrink film for commercial cigarette cartons:

[0105] S31. 50 parts of the modified PLA masterbatch prepared in Example 4, 5 parts of stearic acid, 4 parts of polytrimethylene terephthalate, 3 parts of ADR-4368, 3 parts of oleic acid amide and 20 parts of corn flour are added into a twin-screw extruder with a length-to-diameter ratio of 40:1 and a barrel temperature of 165°C for the first section, 170°C for the second section, 175°C for the third section, 180°C for the fourth section, 175°C for the fifth section and 165°C for the sixth section, and mixed and extruded at 80 r / min, and then cooled by a rotary drum to obtain a cast sheet.

[0106] S32. The cast sheet is longitudinally stretched to 2 times at 80° C., and then rolled and slit to obtain the fully biodegradable heat shrinkable film for commercial cigarette cartons.

[0107] Experimental Example 1

[0108] In order to further verify the superior performance of the fully biodegradable heat shrinkable film for commercial cigarette cartons of the present application, the inventor conducted a series of research experiments. After testing, the performance of the fully biodegradable heat shrinkable film for commercial cigarette cartons obtained in Examples 7 to 9 and Comparative Examples 1 to 3 is shown in Table 1:

[0109] Table 1

[0110]

[0111] Experimental Example 2

[0112] In order to further verify the biodegradability and biosafety of the fully biodegradable heat shrinkable film for commercial cigarette cartons of the present application, the inventor conducted a series of research experiments. After testing, the biodegradability and biosafety of the fully biodegradable heat shrinkable film for commercial cigarette cartons obtained in Examples 7 to 9 and Comparative Examples 1 to 3 are shown in Table 2:

[0113] Table 2

[0114]

[0115] It can be seen from Tables 1 and 2 that the fully biodegradable heat shrinkable film for commercial cigarette cartons provided by the present application has mechanical properties far superior to those of the films obtained by the prior art, and at the same time has good light transmittance, can be used for work with different packaging requirements, and can meet AI image recognition after packaging. At the same time, the biodegradability of the fully biodegradable heat shrinkable film for commercial cigarette cartons provided by the present application also far exceeds that obtained by the prior art. At the same time, it contains no heavy metals and has low biological toxicity. It will not cause any impact on the human body or the environment during or after use, and can be applied to multiple fields in the future.

[0116] The above is only a preferred embodiment of the present disclosure. It should be understood that the present disclosure is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present disclosure, and should be within the scope of protection of the claims attached to the present disclosure.

Claims

1. A fully biodegradable heat shrinkable film for commercial cigarette cartons, characterized in that: In parts by weight: Wherein, the method for preparing the modified PLA masterbatch comprises: The toughening plasticizer is first dried to obtain a dry toughening plasticizer; The dry toughening plasticizer, polylactic acid, lipase, cellulose, inorganic calcium powder, epoxy soybean oil and antioxidant are first mixed and then discharged to obtain a plastic melt; and The plastic melt is subjected to a first cooling, a second drying, and pelletizing and packaging to obtain the modified PLA masterbatch.

2. The fully biodegradable heat shrinkable film according to claim 1, characterized in that: The modified PLA masterbatch comprises, by weight:

3. The fully biodegradable heat shrinkable film according to claim 1, characterized in that: The lubricant includes stearic acid; The chain extender includes ADR-4368; The opening agent includes at least one of EBS, oleic acid amide and polyethylene wax; The filler masterbatch includes at least one of corn flour and talcum powder; The lipacid enzyme includes Candida lipase; Therefore, the antioxidant includes antioxidant 1076.

4. The fully biodegradable heat shrinkable film according to claim 1, characterized in that: The first mixing is carried out in a first twin-screw extruder, the aspect ratio of the first twin-screw extruder is 40:1, the barrel temperature of the first twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the first twin-screw extruder is 80-90r / min.

5. The fully biodegradable heat shrinkable film according to claim 1, characterized in that: The method for preparing the toughening plasticizer comprises: Adding diol and catalyst system to dibasic acid to carry out esterification reaction to obtain milky white homogeneous liquid; and Lactic acid is added to the milky white homogeneous liquid to carry out an ester exchange polycondensation reaction to obtain the toughening plasticizer.

6. The fully biodegradable heat shrinkable film according to claim 5, characterized in that: The molar ratio of the dibasic acid to the diol is 1:1 to 3; And / or, the weight ratio of the lactic acid to the milky white homogeneous liquid is 1:4-6.

7. The fully biodegradable heat shrinkable film according to claim 5, characterized in that: The diol includes ethylene glycol; The dibasic acid includes succinic acid; The catalyst system comprises a system consisting of isopropyl titanate and methanesulfonic acid.

8. The fully biodegradable heat shrinkable film according to claim 5, characterized in that: The esterification reaction is carried out under normal pressure nitrogen environment, the temperature of the esterification reaction is 190° C. to 210° C., and the time of the esterification reaction is 5 to 6 hours; The transesterification polycondensation reaction is carried out under a 40 kPa nitrogen environment, the temperature of the transesterification polycondensation reaction is 210° C. to 240° C., and the time of the transesterification polycondensation reaction is 1 to 3 hours.

9. A method for preparing a fully biodegradable heat shrinkable film according to any one of claims 1 to 8, characterized in that: The following steps are involved: The modified PLA masterbatch, lubricant, poly(trimethylene terephthalate), chain extender, opening agent and filler masterbatch are subjected to a second mixing, extrusion and a second cooling to obtain a cast sheet; and The cast sheet is subjected to biaxial stretching, winding and slitting to obtain the fully biodegradable heat shrinkable film.

10. The method according to claim 9, characterized in that The second mixing is carried out in a second twin-screw extruder, the aspect ratio of the second twin-screw extruder is 40:1, the barrel temperature of the second twin-screw extruder is 165°C in the first section, 170°C in the second section, 175°C in the third section, 180°C in the fourth section, 175°C in the fifth section, and 165°C in the sixth section, and the rotation speed of the second twin-screw extruder is 80-90r / min.